RAB-5 Controls the Cortical Organization and Dynamics of PAR Proteins to Maintain C. elegans Early Embryonic Polarity - Hyenne, Vincent; Tremblay-Boudreault, Thierry; Velmurugan, Ramraj; Grant, Barth D.; Loerke, Dinah; Labbé, Jean-Claude (PLOS ONE, 2012)
In all organisms, cell polarity is fundamental for most aspects of cell physiology. In many species and cell types, it is controlled by the evolutionarily conserved PAR-3, PAR-6 and aPKC proteins, which are asymmetrically localized at the cell cortex where they define specific domains. While PAR proteins define the antero-posterior axis of the early C. elegans embryo, the mechanism controlling their asymmetric localization is not fully understood. Here we studied the role of endocytic regulators in embryonic polarization and asymmetric division. We found that depleting the early endosome regulator RAB-5 results in polarity-related phenotypes in the early embryo. Using Total Internal Reflection Fluorescence (TIRF) microscopy, we observed that PAR-6 is localized at the cell cortex in highly dynamic puncta and depleting RAB-5 decreased PAR-6 cortical dynamics during the polarity maintenance phase. Depletion of RAB-5 also increased PAR-6 association with clathrin heavy chain (CHC-1) and this increase depended on the presence of the GTPase dynamin, an upstream regulator of endocytosis. Interestingly, further analysis indicated that loss of RAB-5 leads to a disorganization of the actin cytoskeleton and that this occurs independently of dynamin activity. Our results indicate that RAB-5 promotes C. elegans embryonic polarity in both dynamin-dependent and -independent manners, by controlling PAR-6 localization and cortical dynamics through the regulation of its association with the cell cortex and the organization of the actin cytoskeleton.